2014
DOI: 10.1155/2014/931410
|View full text |Cite
|
Sign up to set email alerts
|

Forearm Compartment Syndrome Caused by Reperfusion Injury

Abstract: Compartment syndrome is commonly seen following lower extremity ischemia. However, upper extremities' compartment syndrome, especially after any vascular surgical procedures, is infrequent. Herein we report a case of an acute forearm compartment syndrome that was developed after delayed brachial artery embolectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…14 After embolectomy, patients must be monitored closely for development of compartment syndrome caused by reperfusion and treated accordingly. 15 …”
Section: Upper Extremity Ischemiamentioning
confidence: 99%
“…14 After embolectomy, patients must be monitored closely for development of compartment syndrome caused by reperfusion and treated accordingly. 15 …”
Section: Upper Extremity Ischemiamentioning
confidence: 99%
“…Delayed diagnosis puts the patient at increased risk of life-threatening reperfusion syndrome following revascularisation. As described by Sayar, Ozer, and Mataraci (2014), reperfusion syndrome includes both local (compartment syndrome, ischaemic contractures) and systemic effects (including hyperkalaemia, acidosis, renal, hepatic, and pulmonary insufficiency, arrhythmias, and consequent cardiac arrest). Patients with delayed diagnosis are also more likely to require fasciotomies, due to the increased likelihood of compartment syndrome.…”
Section: Secondary Care Managementmentioning
confidence: 99%
“…Compartment syndrome is a pathological condition caused by increased pressure within a closed fascial compartment, which may cause ischaemia, and result in functional loss of muscle and nerve tissue 1. There are various causes of compartment syndrome and many studies have concluded that fractures are the commonest; for example, they accounted for 69% of cases in a study by McQueen et al 2.…”
Section: Introductionmentioning
confidence: 99%
“…Acute compartment syndrome, which is the focus of this report, is often secondary to trauma; the pressure rise occurs from bleeding or inflammation. However, chronic compartment syndrome occurs when excessive exercise results in increased pressure within an enclosed fascial compartment in a susceptible individual 1 3…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation